The lactate sensor NDRG3 decelerates ER-to-Golgi transport through interaction with the long isoform of syntaxin-5 - Pia E. Ferle; Niklas Krause; Judith Koliwer; Jörn Michael Völker; Fabia Becker; Alexander Hillebrand; Leonie F. Schröder; Stefanie Jäger; Seby Edassery; Dali Liu; Nevan J. Krogan; Jeffrey N. Savas; et al. (Proceedings of the National Academy of Sciences, 2025)
BET1, GOSR2, and STX5 variants can cause fatal inherited diseases, including epilepsies, muscular dystrophy, and multisystemic disorders. Together with Sec22b, they form a SNARE complex that mediates fusion of ER-derived vesicles with the ER-Golgi-intermediate compartment and the cis -Golgi. The Sec1/Munc18 protein SCFD1/Sly1 accelerates ER-to-Golgi SNARE complex assembly and membrane fusion, but much less is known about downregulation of ER-to-Golgi trafficking under cellular stress conditions. Here, we identify the lactate and hypoxia sensor protein NDRG3 as a binding partner of the ER-to-Golgi SNARE complex. NDRG3 binds via its C-terminal domain to the N-terminal domain of the long isoform of Stx5, thereby impairing ER-to-Golgi trafficking under hypoxic conditions and elevated intracellular lactate levels. In NDRG3-deficient cells, hypoxia- and lactate-induced inhibition of ER-to-Golgi trafficking is abolished. Our work identifies NDRG3 as a negative regulator of ER-to-Golgi SNARE complex function, mechanistically linking hypoxia and lactate to membrane trafficking in the secretory pathway.